2006
DOI: 10.1152/ajpendo.00300.2005
|View full text |Cite
|
Sign up to set email alerts
|

No effect of menstrual cycle on myofibrillar and connective tissue protein synthesis in contracting skeletal muscle

Abstract: -We tested the hypothesis that acute exercise would stimulate synthesis of myofibrillar protein and intramuscular collagen in women and that the phase of the menstrual cycle at which the exercise took place would influence the extent of the change. Fifteen young, healthy female subjects were studied in the follicular (FP, n ϭ 8) or the luteal phase (LP, n ϭ 7, n ϭ 1 out of phase) 24 h after an acute bout of one-legged exercise (60 min of kicking at 67% W max), samples being taken from the vastus lateralis in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 38 publications
6
77
1
Order By: Relevance
“…It cannot be excluded that the present findings are a result of secondary hormonal responses of the OC intake and not a direct effect of estradiol (synthetic or endogenous estradiol). In an earlier study, an ϳ3-fold increase in muscle collagen FSR was observed 24 h postexercise in eumenorrheic women in either the follicular phase or luteal phase of the menstrual cycle (45). This does not support a direct inhibiting effect of estradiol.…”
Section: Effects On Muscle Collagen Synthesismentioning
confidence: 75%
“…It cannot be excluded that the present findings are a result of secondary hormonal responses of the OC intake and not a direct effect of estradiol (synthetic or endogenous estradiol). In an earlier study, an ϳ3-fold increase in muscle collagen FSR was observed 24 h postexercise in eumenorrheic women in either the follicular phase or luteal phase of the menstrual cycle (45). This does not support a direct inhibiting effect of estradiol.…”
Section: Effects On Muscle Collagen Synthesismentioning
confidence: 75%
“…A 15-to 25 mg piece of muscle tissue was used for isolating the myofibrillar and collagen proteins using a solubility/centrifugation procedure used elsewhere (5,23,25,68,70,71). Briefly, muscle samples were homogenized in 1 ml ice-cold buffer containing 0.15 M NaCl, 5 mM EDTA, 0.1% Triton X-100, and 0.02 M Tris (pH 7.4) using an automatic homogenizer (FastPrep 120A-230; Thermo Savant, Holbrook, NY).…”
Section: Sample Preparation and Analysesmentioning
confidence: 99%
“…Data are means Ϯ SE. exercise on muscle collagen FSR has previously been shown (5,23,47,68,70,71), only the effect of contraction type (lengthening vs. shortening contractions) but not intensity has been investigated earlier. Contraction types induced slightly divergent improvements in the FSR of the mature human muscle collagen protein in the first hours after exercise (23,71).…”
Section: Intramuscular Collagen Protein Synthesis Ratementioning
confidence: 99%
“…These findings suggests that exogenous hormones may in uence the anabolic response of muscle to resistance exercise. e myo brillar protein fractional synthetic rate (FSR) does not vary across the menstrual cycle 38 , however H et al 39 demonstrated that females using a third generation OC (30 µg EE and 0.0075 g Gestogen) had a lower FSR than second generation users (35 µg EE and 0.25 mg Norgestimate) and no hormone controls. is suggests that the exogenous synthetic component of contraceptives can a ect protein synthesis, unlike endogenous female reproductive hormones.…”
Section: Is There a Relationship Between Hormonal Contraceptives And mentioning
confidence: 99%